ANALYSIS OF TEACHER PROFESSIONALISM IN INCREASING THE QUALITY OF EDUCATION IN MADRASAH - Sari Atika Parinduri; Desi Ramanda Sari (RADJA PUBLIKA, 2021)
This study uses qualitative research with a case study approach and the research instruments used are observation, interviews, and documentation. The results of the research in this thesis, Analysis of Teacher Professionalism in Improving the Quality of Education in Madrasah Aliyah Hidayah Private, Bandar Tengah Village, Bandar Khalipah District, can be seen from 4 (four) aspects of competence, namely: pedagogic competence, namely the teacher's ability to manage learning for students, includes curriculum development, personality competencies, namely personality abilities that master adult and exemplary personal knowledge, develop themselves independently and sustainably. Social competence, namely communication with the community, getting along effectively with fellow professions/ educators, students and guardians of students, polite with the community, and professional competence, namely mastering material in a structured and conceptual manner, a scientific mindset supports the subjects being taught, mastery in media skills and supporting teaching materials. Professionalism in improving the quality of education at Hidayah Private Madrasah Aliyah, Bandar Tengah Village, Bandar Khalipah District, has been carried out quite well.